Description of immatures of Mesomphalia gibbosa (Fabricius, 1781) and Mesomphalia turrita (Illiger, 1801) (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini) - Simões, Marianna V. P.; Monné, Marcela L. (Zootaxa, 2014)
Immatures of Mesomphalia gibbosa (Fabricius, 1781) and Mesomphalia turrita (Illiger, 1801) (Coleoptera, Chrysomelidae, Cassidinae, Mesomphaliini) are described based on specimen collections from Rio de Janeiro state, Brazil. The last-instar larva and pupal exuviae of M. gibbosa (Fabricius, 1781) and the eggs, first-instar larva, and pupa of M. turrita (Illiger, 1801) are described, photographed and illustrated, with emphasis on chaetotaxy. Additional notes on their biology are presented.